2013
DOI: 10.1136/heartjnl-2012-303349
|View full text |Cite
|
Sign up to set email alerts
|

Suitability for subcutaneous defibrillator implantation: results based on data from routine clinical practice

Abstract: After 5 years of follow-up, approximately 55% of the patients would have been suitable for an S-ICD implantation. Several baseline clinical characteristics were demonstrated to be useful in the selection of patients suitable for an S-ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 30 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…A recent study demonstrated that approximately 60% of the patients with a transvenous ICD without a preexistent indication for pacing could be suitable for S-ICD implantation. 10 This implies that, following our finding that 93% of the patients have an appropriate TMS-ECG, more than 50% of all ICD patients without a preexistent pacing indication could be eligible for S-ICD implantation. On the other hand, the S-ICD cannot be used as first line therapy in more than 7% of the patients, with even higher rates in selected populations such as HCM and obese patients.…”
Section: Prevalence Of S-icd Suitabilitymentioning
confidence: 92%
“…A recent study demonstrated that approximately 60% of the patients with a transvenous ICD without a preexistent indication for pacing could be suitable for S-ICD implantation. 10 This implies that, following our finding that 93% of the patients have an appropriate TMS-ECG, more than 50% of all ICD patients without a preexistent pacing indication could be eligible for S-ICD implantation. On the other hand, the S-ICD cannot be used as first line therapy in more than 7% of the patients, with even higher rates in selected populations such as HCM and obese patients.…”
Section: Prevalence Of S-icd Suitabilitymentioning
confidence: 92%
“…This raises the question as to what proportion of patients who would qualify for an S-ICD would ultimately require pacing or ATP & hence need conversion of their device to a transvenous system. A recent Dutch study of ICD recipients reviewed 463 patients followed up over a median of 3.4 years between 2002-11 [28]. It was demonstrated that 55.5 % (95 % CI 52.0 % to 59.0 %) of single or dual chamber ICD recipients would have been suitable for an initial S-ICD implantation after 5 years, i.e.…”
Section: Limitations Of the S-icd: Bradycardia Pacing And Anti-tachycmentioning
confidence: 99%
“…It becomes a less invasive option for patients in whom TV-ICD implantation is surgically impossible. It is estimated that up to 55% of patients in routine clinical practice needing an ICD are potential candidates for a subcutaneous device [14,15]. However, to maximize clinical outcome and cost/benefit ratio, it is fundamental to choose candidates that can benefit most, taking into account both patient and device characteristics.…”
Section: Discussionmentioning
confidence: 99%